A STUDY OF WOMEN'S PARTICIPATION IN NATIONAL MOVEMENT WITH SPECIAL REFERENCE TO BIHAR. - Kumar, Manish; Shankar, Biklendu (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Women played a pivotal role in the history of India's independence, stepping out of their homes to join protests, endure arrests, and face hardships, including brutalities. Their contributions not only energised the movement but also left a lasting impact on the struggle for freedom. It is important to acknowledge the significant contributions of women in national movements. They fought with remarkable spirit and courage, playing an incredible and vital role in both the freedom movement and the nation's awakening. Women not only sacrificed their lives but also endured numerous challenges. One such example is Rani Laxmi Bai, a fearless leader who fought valiantly against British rule during India's struggle for independence. Women in India made significant contributions to the freedom struggle by actively participating in major movements like non-cooperation, civil disobedience, and Quit India, etc. This study highlights the activism of prominent figures such as Sarojini Naidu, Aruna Asaf Ali, and Sucheta Kripalani, along with other local leaders who played key roles in mobilising both rural and urban communities against the British.